2018
DOI: 10.1515/physio-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity as the main factor affecting body composition of the visually impaired

Abstract: Introduction. The aim of the study was to determine how physical activity affected the physical fitness and body composition of the blind and visually impaired. Methods. The study included 28 male students from the Lower Silesia Special Educational Centre No. 13 for the Blind and Visually Impaired in Wroclaw, aged 18-22 years, with disability degree certificates. The subjects were divided into two groups: physically active men (TR, n = 15) and physically inactive men (NTR, n = 13). The researchers assessed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Therefore, the latest WHO guidelines, in addition to the recommendations for physical activity, pay great attention to the need to limit sedentary lifestyle and replace it with even low-intensity activity [3] Limiting physical activity affects the quality of life, as well as health. Adequate physical activity not only influences one's mental health, but also helps maintain a correct body mass [4][5][6]. This plays a vital role in the preservation of health.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the latest WHO guidelines, in addition to the recommendations for physical activity, pay great attention to the need to limit sedentary lifestyle and replace it with even low-intensity activity [3] Limiting physical activity affects the quality of life, as well as health. Adequate physical activity not only influences one's mental health, but also helps maintain a correct body mass [4][5][6]. This plays a vital role in the preservation of health.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that visual impairment is associated with a low quality of life [3], as it causes a variety of difficulties in daily activities and limits interactions and independence. One significant problem that this particular population has faced is a sedentary lifestyle due to difficulties in transportation and mobility [4].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, moderate physical activity (PA) is essential, in addition to a healthy diet and better mental health. In fact, it has been reported that additional PA has a positive effect on body composition and physical fitness in people with visual impairments [ 4 ].…”
Section: Introductionmentioning
confidence: 99%